Réponses

Meilleure réponse !
  • Utilisateur Brainly
2014-03-30T13:34:01+02:00
Ex 3 :
soit A(-8;-5) , B(-5;-1) , C(-1;0) , D(-0,5;-1) , E(0;1) , F(1;0) , G(8;-2)
on construit alors une courbe Cf passant par les points A,B,C,D,E,F,G

Ex 4 :
a²+b²+c²+d²=ab+bc+cd+da
(a+b)²=a²+b²+2ab
(c+d)²=c²+d²+2cd
donc 2ab+2cd=ab+bc+cd+da
donc ab+cd=bc+ad
donc ab-ad-bc+cd=0
donc a(b-d)-c(b-d)=0
donc (a-c)(b-d)=0
donc a-c=0 ou b-d=0
donc a=c ou b=d

alors si a=c ou bien si b=d on obtient
a²+b²+a²+b²=ab+ab+ab+ab
donc a²+b²=2ab
donc a²-2ab+b²=0
donc (a-b)²=0
donc a-b=0
donc a=b

or a=c et b=d
ainsi a=b=c=d